ICMI dan Surat Kabar Republika: Studi Tindakan ICMI terhadap Revivalisme Islam di Indonesia - Suntara Guci Pangestu; Widiati Isana (UIN Sunan Gunung Djati Bandung, 2021)
Revivalism is used as a tool by modernists to respond to the domination of a group that eliminates the original values of the dominated people, ICMI was born as a new-political power to become the backbone of Muslims in offensive movements to combat the mushrooming boredom. Neo-revivalism was used as an ICMI maneuver during the New Order era, to return Islam to a social order, which was purely in accordance with past texts. ICMI gave birth to Republika Newspaper, a product to support the action; propaganda and columns to accommodate the aspirations of Muslims